Empirical Insights on Gender-Based Computer Font Preference of Dyslexic Juvenile Learners: A Case Study in Sarawak, Malaysia - Mohd Khairulazwan, Sulaiman; Irwandi, Hipiny; Hamimah, Ujir (2022)
The ongoing Covid-19 pandemic necessitates for a continuous deployment of online teaching and learning (T&L) approach in Malaysia, either in full or hybrid mode. Unfortunately, dyslexic juvenile learners are also imposed with this unfavorable arrangement since all schools nationwide, including those accommodating for special needs education, are fully or partially closed. Thus, it is imperative for the online T&L materials to be designed to optimize the retention of dyslexic juvenile learners’ focus and interest. We are specifically interested in the choice of computer font (and its properties) for dyslexic juvenile learners. In this research, we conducted a quantitative survey involving N=16 juvenile dyslexic learners registered with Dyslexia Association of Sarawak. The survey recorded their individual preference for font type, properties, and color scheme. Our subjects did not demonstrate any gender-specific preferences, except for the choice between high and low contrast text.